Peran Teknologi Digital dalam Membangun Model Bisnis Berkelanjutan Pada Umkm di Era Digital - Karina Kamista; Masyhuri, Masyhuri (Journal of Economic and Business Advancement, 2026)
This study examines the role of digital technology in developing sustainable business models for Micro, Small, and Medium Enterprises (MSMEs) in the digital era through a qualitative literature review approach. The analysis synthesizes multidisciplinary perspectives from digital economy and strategic management studies to identify the implications of digital transformation for MSME sustainability. The findings indicate that digital technologies contribute to operational efficiency, business adaptability, market responsiveness, and long-term competitiveness through the integration of digital platforms and data-driven business processes. The study concludes that digital technology functions as a strategic foundation for constructing adaptive, innovative, and sustainable MSME business models in the contemporary digital economy.